The role of competence beliefs, task value, and achievement goals in predicting mathematics anxiety - Rovan, Daria (2011)
This paper analyses the role of competence beliefs, subjective value, and achievement goals in the prediction of elementary school students’ mathematics anxiety, considering students’ gender, grade and previous mathematics achievement. A sample of 297 fifth to eight-grade students from two elementary schools in Zagreb, Croatia participated in the study. Students answered a questionnaire on motivational beliefs and anxiety in mathematics at the end of school year. Results showed that mastery-avoidance goal was the strongest predictor of mathematics anxiety followed by competence beliefs, interest and attainment value. Motivational beliefs predicted mathematics anxiety above and beyond previous mathematics achievement. Students pursuing mastery-avoidance goals were more prone to mathematics anxiety. In addition, students who had stronger competence beliefs, higher interest in mathematics and higher attainment value were less likely to show mathematics anxiety. This research advances our understanding of how individual differences in motivational beliefs may influence mathematics anxiety. Understanding the motivational background of mathematics anxiety, teachers can make easier to the children to overcome this problem.